COVID-19 VACCINATION EDUCATION WITH MEDIA LEAFLET IN SEGOROYOSO 2 RT 2 PLERET BANTUL - Zulfa Indriyani, Sheilla; Emma Dwi Jatmika, Septian (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The Covid-19 vaccination is one of the efforts made by the government to suppress the rate of Covid-19, but in the implementation of this Covid-19 vaccination, there are still obstacles in the form of low vaccination coverage. Based on the situation analysis conducted at Segoroyoso 2RT 2, the number of people who have received the Covid-19 vaccination is still below 50%. For this reason, door-to-door Covid-19 vaccination education was held using leaflets targeting 29 families. This educational activity is carried out through 3 stages, namely: preparation, implementation, and evaluation. At the preparatory stage, a situation analysis is carried out, prioritizing problems and alternative problem-solving. The stage of implementing education by vaccinating Covid-19 using leaflet media is carried out on November 14-15, 2021 with a target of 29 families. The evaluation stage was carried out by conducting pretest and posttest activities, the results of which increased knowledge of vaccination for residents of Segoroyso 2 RT by 28%.